Cryptography, Steganography, & Digital Watermarking for Text Documentation - Nurul Suzulyana, Zulkifley; Nur Haziqah, Zainal Abidin; Nurul Zulaikha, Sulaini; Muhamad Khairil Amir, Mohamad Nawi; Syifak Izhar, Hisham (Universiti Malaysia Pahang, 2020)
This paper is about three techniques used in securing text documents, cryptography, steganography, and digital watermarking. This review and comparison are made based on the available technologies and research in order to protect and secure all the documents including the patients’ personal information. At the end, this paper suggests the related techniques that can be implemented by the hospital management systems, which is a combination of digital watermarking and steganography.